2017
DOI: 10.1039/c7py01263b
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the reaction mechanism of the thiol–epoxy addition initiated by nucleophilic tertiary amines

Abstract: The mechanism of thiol–epoxy reactions has been analyzed from a theoretical point of view and modelled using experimental kinetic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 45 publications
(115 reference statements)
4
73
0
Order By: Relevance
“…At temperatures as low as 30 °C, in the first process one can appreciate an induction period of about 90 min that indicates that there should be enough time to inject the sample in the mould cavity before the reaction starts. It is also observed that the first process has a very strong autocatalytic behaviour, as reported previously, and therefore there is a serious risk of temperature runaway if the programmed temperature is too high. Given that crosslinking would take place entirely in the second curing stage and that the first curing process is much faster and more exothermic than the second one, the key point to ensure uniform crosslinking during processing of the composite part will be to control the exothermicity during the first curing process, so that the second curing process does not start.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…At temperatures as low as 30 °C, in the first process one can appreciate an induction period of about 90 min that indicates that there should be enough time to inject the sample in the mould cavity before the reaction starts. It is also observed that the first process has a very strong autocatalytic behaviour, as reported previously, and therefore there is a serious risk of temperature runaway if the programmed temperature is too high. Given that crosslinking would take place entirely in the second curing stage and that the first curing process is much faster and more exothermic than the second one, the key point to ensure uniform crosslinking during processing of the composite part will be to control the exothermicity during the first curing process, so that the second curing process does not start.…”
Section: Resultssupporting
confidence: 80%
“…Both reactions are depicted in Scheme (right‐hand side). The reaction mechanisms of nucleophile‐initiated thiol–epoxy polymerization and epoxy homopolymerization have been recently discussed in detail elsewhere . Because the kinetics of the second process are much slower than the first one, it has been possible to develop recently a new family of dual‐curable thermosetting materials that have found, so far, an application in shape‐memory devices …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Epoxy resins are commonly cured by active hydrogen-containing compounds such as phenol novolac, bisphenol A novolac, dicyandiamide, and diamine [4][5][6][7][8][9][10][11][12][13]. However, the reaction product from active hydrogen and epoxy lead to a secondary alcohol.…”
Section: Introductionmentioning
confidence: 99%